The Market Traders' Perceptions of Land and Building Tax Collection (Case Study of Traders at Cicalengka Market) - Allisya Syiffa Nalurita (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
Cicalengka District is one of the land and building tax revenue bases which helps process collections in the District. Bandung. This research aims to determine community perceptions as measured by observation, questionnaires with a Likert scale and interviews regarding land and building tax payments. The target of this research is the Sabilulungan Cicalengka Healthy Market traders as objects who experience direct benefits from regional development who live in Cicalengka District, totaling 1875 shops or traders. Based on research findings, there is a perception that awareness of the level of land and building tax (PBB) payments in Cicalengka District is quite good. Even though the available data is only 51% of taxpayers who have paid in 2021. From the results of observations, questionnaires and interviews with Cicalengka market traders, on the contrary, taxpayers in the District have a poor perception regarding their awareness of paying taxes. So there needs to be an effort to help the community become better at understanding paying taxes in the context of smooth national development.